Cancer-related venous thromboembolism: epidemiology and risk factors - Blix, Kristine (UiT The Arctic University of Norway, 2014)
Papers number I and II of the thesis are not available in Munin: I. Blix K, Brækkan SK, le Cessie S, Skjeldestad FE, Cannegieter SC, Hansen JB: 'The increased risk of venous thromboembolism by advancing age cannot be attributed to the higher incidence of cancer in the elderly: the Tromsø study', Eur J Epidemiol. 2014; 29(4):277-84, available at: http://dx.doi.org/10.1007/s10654-014-9902-7 II. Blix K, Severinsen MT, Brækkan SK, Jensvoll H, Dziewiecka O, Kristensen SR, Overvad K, Tjønneland A, Næss IA, Hammerstrøm J, Rosendaal FR, Cannegieter SC, Hansen JB:'Cancer-associated venous thromboembolism in a general population – the Scandinavian Thrombosis and Cancer (STAC)', manuscript. The association between cancer and venous thromboembolism (VTE) was described already in the 19th century and cancer has later been acknowledged as one of the most important risk factors for VTE. Population-based studies on the subject with information about confounders and validated endpoints are lacking. The first aim of this thesis was to estimate the frequency of VTE among cancer patients in a population-based cohort study and assess the risk among cancer patients compared to a cancer-free reference population. Secondly, we wanted to investigate whether the level of leukocytes and platelets at inclusion influenced the future risk of VTE in cancer patients and in those who remained cancer-free. The fourth survey of the Tromsø study (Tromsø IV) was applied in all four papers of this thesis. The Tromsø Study is a prospective study of adult inhabitants of Tromsø. In Tromsø IV (1994-95), information from more than 27 000 subjects were collected by physical examination, self-administrated questionnaires and blood tests, and VTE events were registered throughout 2010. Information about cancer was provided by the Cancer Registry of Norway. In paper II, the Tromsø IV cohort was merged with two additional Scandinavian cohorts (i.e. HUNTII and DCH) and 137 000 subjects were included in the study. VTE occurred among 3-5 % of the cancer ...